Emotional climate: a bibliometric analysis of the psychological consequences of climate change - Momenpour, Yadgar; Choobchian, Shahla (Frontiers in Psychology, 2025)
Research on climate change and its impact on individuals' emotions are receiving increasing attention. Therefore, it is crucial to evaluate the current state of this research and predict future trends to offer greater clarity for researchers and decision-makers. This study aims to analyze the co-authorship network, bibliographic coupling, and co-word analysis of scientific documents produced by researchers in the Scopus database from 2010 to 2024. This period is characterized by the emergence and conceptual consolidation of emotional responses to climate change in academic research, focusing on the psychological consequences of climate change. A total of 1,333 documents were chosen for analysis after completing the identification and screening processes. This research is applied and descriptive in terms of its scient metric approach and is conducted using co-occurrence word analysis and network analysis techniques. The collected data were analyzed using Excel, and VOS viewer software was utilized to create visual maps. The co-occurrence analysis of high-frequency terms highlighted emerging topics and critical issues related to climate change. The findings emphasize the connection between clusters related to climate change and climate justice with the core cluster of humanity and human emotions, highlighting the emerging nature of this research domain. The thematic clusters identified further emphasize the significance and novelty of climate-related emotions and the organization of related research. This review can serve as a roadmap for future research, planning, and decision-making in the area of climate change and its associated impacts.